Investing in energy : a primer on the economics of the energy industry - Bern, Gianna (Hoboken, N.J. : Bloomberg Press, 2011)
"An energy industry researcher and investment advisor provides a fresh perspective on the economics of energy From major players in the energy industry, such as big oil, to the emerging cap-and-trade market, no other book offers a more complete overview of the energy industry, specifically its economic and financial intricacies, than Investing in Energy: A Primer on the Economics of the Energy Industry. Details how to value and invest in the four big energy sectors: oil, gas, power, and green Describes key financial considerations for the energy sectors, including credit metrics, the importance of liquidity, cash flow, and capital expenditures From Bloomberg, a leading provider of the most up-to-date business news and financial data A comprehensive guide to the economics of the energy industry, Investing in Energy will prove an invaluable resource for traditional energy investors looking to expand into new areas, as well as for eco-investors looking to better understand how energy markets function"--
Περιέχει ευρετήριο.
Keywords: Energy industries -- Finance; Investments